2013
DOI: 10.1093/jmcb/mjt038
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2 receptor α promotes tumor growth through an autoregulatory feedback pathway

Abstract: Tobacco smoking can cause a number of cancers. The role of thromboxane synthase (TxAS) in smoking-related cancers is largely unknown. In this study, 37 pairs of tumor and non-tumor lung tissues of non-small-cell lung cancer, 5 lung cancer cell lines, and a mouse tumor model were used to study TxAS and its related molecules. A mouse model of smoking carcinogen 4-methylnitrosamino-1-3-pyridyl-1-butanone (NNK)-induced lung tumor showed an increase in TxAS. Thromboxane A2 receptor (TP) was aberrant in lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…As expected, several studies showed that TxA 2 antagonist, TxAS inhibitor, or TP antagonist could inhibit cancer cell growth and induce apoptosis by increasing the ROS level, inhibiting the NF-κB pathway, increasing the nuclear p27 level, or blocking ERK/CREB signaling in lung cancer, bladder cancer, and glioblastoma [83,[85][86][87][88][89][90][91].…”
Section: Nnk Regulates Gene Expression Through Dna Methyltransferase mentioning
confidence: 69%
See 1 more Smart Citation
“…As expected, several studies showed that TxA 2 antagonist, TxAS inhibitor, or TP antagonist could inhibit cancer cell growth and induce apoptosis by increasing the ROS level, inhibiting the NF-κB pathway, increasing the nuclear p27 level, or blocking ERK/CREB signaling in lung cancer, bladder cancer, and glioblastoma [83,[85][86][87][88][89][90][91].…”
Section: Nnk Regulates Gene Expression Through Dna Methyltransferase mentioning
confidence: 69%
“…More explicitly, NNK activates PI3K/AKT and ERK pathways through TP, phosphates CREB, induces the expressions of PCNA and Bcl-2, and thereby promotes lung cancer cell survival [75]. The mechanism by which NNK induces the expression of TxAS has previously been explored [83], whereby NNK increases the TPα protein level and increases the TxAS transcription via the COX-2/ERK/NF-κB pathway. The increased TxAS synthesized new TxA 2 , and further activated TPα, which formed an autoregulatory feedback loop for TPα activation.…”
Section: Nnk Regulates Gene Expression Through Dna Methyltransferase mentioning
confidence: 99%
“…Two lung adenocarcinoma cell lines, A549 and NCI-H23, which have been widely used in cancer research, were detected without any transfection in our previous reports [1,11]. It was found that both TPα and TxAS are abundant in A549 but limited in NCI-H23 cells.…”
Section: Discussionmentioning
confidence: 87%
“…We stably transfected A549 cells with TPα for the three following reasons. First, TPα is believed to facilitate lung cancer growth, invasion and metastasis [8,9,[11][12][13]. Second, the effects of both glycyrrhizin and cisplatin are related to the TxA2 pathway [1,5,15,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation